Les conceptions des parents de scripteurs débutants relativement à l’apprentissage de l’écriture - Lavoie, Natalie (Canadian Journal of Applied Linguistics, 2002)
This study identifies parents’ perceptions about children’s development and the factors that influence these perceptions. For this purpose, a 15-item questionnaire was elaborated and filled out by 1103 parents of grade one and two children. Results show that parents’ perceptions are consistent with an emergent perspective in relation to this learning process, i.e. they think that in an informal way, their children learn several things at home regarding writing. It was also noted that parents of grade two children are further supportive of an emergent perspective than parents of grade one children an that the education level of the participant influenced their perceptions on learning to write. Therefore, the better educated parents (university level) showed perceptions more consistent with an emergent perspective as opposed to parents with a lower education (college, high school or elementary school level). Results also indicate a difference between the fathers’ and the mothers’ answers, the mothers’ answers being more consistent with an emergent perspective.